Respiratory burst oxidase of fertilization. - Heinecke, J W (1989)
Partially reduced oxygen species are toxic, yet sea urchin eggs synthesize H2O2 in a "respiratory burst" at fertilization, as an extracellular oxidant to crosslink their protective surface envelopes. To study the biochemical mechanism for H2O2 production, we have isolated an NADPH-specific oxidase fraction from homogenates of unfertilized Strongylocentrotus purpuratus eggs that produces H2O2 when stimulated with Ca2+ and MgATP2-. Concentrations of free Ca2+ previously implicated in regulation of egg activation modulate the activity of the oxidase. Inhibitors were used to test the relevance of this oxidase to the respiratory burst of fertilization. Procaine, two phenothiazines, and N-ethylmaleimide (but not iodoacetamide) inhibited H2O2 production by the oxidase fraction and oxygen consumption by activated eggs. The ATP requirement suggested that protein kinase activity might regulate the respiratory burst of fertilization; consonant with this hypothesis, H-7 and staurosporine were inhibitory. The respiratory burst oxidase of fertilization is an NADPH:O2 oxidoreductase that appears to be regulated by a protein kinase; although it bears a remarkable resemblance to the neutrophil oxidase, unlike the latter it does not form O2- as its initial product.